FINITE ELEMENT MODELING OF COMPOSITE MATERIAL FATIGUE STRENGTH - Evgeny Nikolayevich Ziborov; Arkady Nikolayevich Solovyev (Advanced Engineering Research)
Fatigue calculation is of primary importance when designing parts and assemblies made of composite materials to operate under the variable load. The finite element modeling of the representative bulk in the stress-strain state conforming to the operation conditions is considered. The calculation methods of polymer composites high-cycle fatigue is based on it. The calculations are carried out in the paper. The unidirectional reinforced composite obtained through thermal curing of the glass-reinforced epoxide is studied. Mechanical properties of such materials (including fatigue life) to quite a great extent depend on the manufacturing technology. The calculation permitting to estimate changing strength properties for fatigue life under the breach of the technology requirements to the composite components percent is resulted.